Learning lessons from the community response to COVID-19 in Wales. (20th October 2021) - Grey, CNB; Homolova, L; Davies, AR
Abstract: Background: During the pandemic, community action sprang up in response to the health and social consequences of the virus. Communities were driven to support each other and those perceived as vulnerable. Community support and social capital are key for strengthening resilience, and an important contributor to population health. The aim was to explore what factors enabled community-led action in response to need amongst the most deprived areas in Wales during COVID-19. Methods: Mixed-methods approach, with a strong focus on qualitative research with a systems-lens. Quantitative data was collected through a survey of 2500 adults >18 years; living, working or volunteering in Wales engaged in community action, and analysed descriptively. Outcomes were motivation, benefits, current and past activities, barriers, socio-economic characteristics [age, education, employment, postcode], digital volunteerism, resilience [RRC-ARM 12], and health and wellbeing [WEMWBS-14]. Qualitative data was collected in two communities in South Wales from 46 semi-structured interviews with recipients, volunteers, and strategic leads and analysed thematically. This explored determinants and experience of community-led action, levers and drivers, and integration with the wider system. Results: Results are preliminary. They include individual-level factors underlying volunteerism and pro-social behaviour across different categories of volunteer (unstructured, informal, formal) and across national area-level deprivation indicators (WIMD), and perspectives across the system on community-led response and its role in community empowerment in supporting the vulnerable within communities. Conclusions: Improved understanding of the role of community-led action as a protective factor against widening health inequalities during, and in recovery from COVID-19, was brought together to develop and coproduce a framework to empower community-led action and support sustainable integration with existing services. Key messages: Understanding how community-led action sustained and be better supported and integrated into the health, third sector and social support system is important for building resilient communities. Understanding community-led action during COVID-19 will inform how this can best supported to help protect against the longer-term differences in the health, social and economic impact.